Scutellaria lateriflora Extract Supplementation Provides Resilience to Age-Related Phenotypes in Drosophila melanogaster. - Long, D.M.; Martinez, J.; Soumyanath, A.; Kretzschmar, D. (International journal of molecular sciences, 2026)
The human lifespan has increased dramatically over the last few decades; however, reaching older age increases the risk of age-related diseases and ailments. To extend the healthspan, many have turned to supplements, including plant-based remedies used in traditional medicine, to promote healthy aging. One of these is Scutellaria lateriflora L. (S. lateriflora), native to North America, which has traditionally been used to treat anxiety, stress, and insomnia. However, clinical trials addressing its effects are very limited. Furthermore, plant material is intrinsically complex, and the preparation method affects the composition of extracts. We therefore used Drosophila to test whether S. lateriflora can confer resilience against age-related sleep and mobility deficits, using aqueous (SLAq) and ethanol extracts (SLE). Whereas both SLE and SLAq improved mobility, only SLE reduced sleep fragmentation in older males. By testing several flavonoids present in S. lateriflora, we found that the beneficial effects on mobility were mainly due to baicalin, whereas sleep was improved by a wogonin mix. Since neither the extracts nor the compounds extend the lifespan, this suggests that they improve neuronal health and function and do not generally slow down the aging process. This was supported by our finding that neuronal degeneration was reduced by S. lateriflora (SL) supplementation.